HUBUNGAN ANTARA IKATAN PRIMORDIAL, IDENTIFIKASI KEPARTAIAN PEMILIH DAN PEMAHAMAN PROGRAM CALON LEGISLATIF DENGAN PILIHAN POLITIK ETNIS TIONGHOA DI DAPIL DKI JAKARTA III DALAM PEMILU LEGISLATIF DPR RI 2 - Antonio Fernando; Dwi Windyastuti Budi Hendrarti (Jurnal Politik indonesia (Indonesian Journal of Politics), 2021)
Participation of the Chinese community in Indonesian politics has been significant every year. In fact, not only as voters, currently there are Chinese legislative candidates who have successfully passed to the DPR. Therefore, this research was conducted to determine the primordial attachment, party identification, and comprehension of the legislative candidates’ program on the political choices of the Chinese community. This research was conducted using quantitative methods. Data were collected from 250 respondents through a questionnaire with google form which was distributed through social media. The questionnaire contains information needed for research including the choice of the respondent’s party and respondent’s response to statements regarding primordial attachment, party identification, and comprehension of legislative candidates’ program. The results showed that of the three variables, only the comprehension of the legislative candidate’s program had a relationship with Chinese community political choices. These results are in accordance with the theory of voting behavior with a rational approach by Anthony Downs, which assumes that voters in determine their choices will act rationally by considering the pros and cons of choosing a legislative candidate. In other words, the Chinese community who became the respondents in this research were rational because they could calculate the advantages and disadvantages of choosing a candidate by considering the programs offered by the legislative candidate.